Comparative Metrics and Policy Learning: End-of-Life Care in France and the US. Issue 5 (20th October 2019) - Gusmano, Michael K.; Rodwin, Victor G.; Weisz, Daniel; Cottenet, Jonathan; Quantin, Catherine
Abstract: Comparative policy analysis sometimes relies on the use of metrics to foster policy learning. We compare health care for patients at the end of life (EOL) in the US and France. The analysis aims to enable policy makers in both nations to reexamine their own health systems in light of how their counterparts are responding to common concerns about the intensity, quality and cost of EOL care. We find that a higher percentage of French decedents 65 years and over, are hospitalized, yet they spend fewer days in intensive care units (ICUs) than their counterparts for whom data are available (Medicare beneficiaries) in the US. In addition, decedents in the US consult with a higher number of different physicians than their French counterparts. We also compare patterns of hospital use for decedents in EOL care among academic medical centers (AMCs) in the US and France. We find greater variation among French AMCs than among their counterparts in the US.